Pendampingan Coping Strategy Untuk Mengatasi Loneliness Pada Lansia Di Jepang - Dhini Rama Dhania; Ruth Natalia Susanti (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Coping Strategy Intervention to Address Loneliness Among Elderly People in Japan. Japan is known as a developed country with advanced and innovative technology. However, Japan is also facing a hyper-aged population issue, which has led to various social problems, including loneliness among older adults. Loneliness has been associated with phenomena such as hikikomori (social withdrawal), kodokushi (lonely death), and jisatsu (suicide). In some cases, loneliness may encourage maladaptive coping strategies, including impulsive or reckless behaviors. Therefore, this community service program aims to help elderly individuals develop adaptive coping strategies to manage loneliness and achieve a more positive aging process. The program applies an emotion-focused coping approach, which emphasizes managing emotional responses to stressful situations. The intervention introduces the 2P Technique, consisting of the Reflection Technique and Diversion Technique, to support emotional regulation and adaptive coping among the elderly.